Digital technologies and the nature and routine intensity of work: Evidence from Hungarian manufacturing subsidiaries - Andrea Szalavetz (European Trade Union Institute (ETUI), 2021)
This paper explores the impact of digital technologies on the nature and routine intensity of shopfloor work, the ways in which digital technologies exert their effects and the factors moderating the outcomes of digitalisation in respect of work. The effect of technology cannot be limited to a dichotomy of increasing versus decreasing degrees of routine. Instead, there are basic scenarios as far as the routine content of activities is concerned: a) no change in routine; b) increased routine; c) transformed routine; d) reduced routine. More specifically, drawing on data from Hungarian companies, we discuss the multiple ways that technology affects the nature and routineness of work. These include (i) workload and intensity of work; (ii) the degree to which tasks can be explicitly defined, measured and codified; (iii) task spectrum, i.e. the variability, complexity and diversity of work tasks; (iv) the composition and amount of skills required for task execution; (v) the importance of experience or tacit knowledge for task execution; and (vi) the value added of work tasks. Evidence indicates that the qualitative enrichment of shopfloor work and digital technology-induced reduction in the routine content of job tasks apply only to relatively skilled employees, albeit not exclusively in high-level shopfloor functions. It is argued that the beneficial effects of digital technologies materialise only if employees are skilled enough to be upskilled and become engaged not only in digitally-assisted but also in digitally-augmented, high-value activities. Finally, positive developments in the nature of work require that employees' work tasks be reorganised, work design and work practices modified and employees upskilled: thus, they are contingent on conscious organisational and human resources management. Without these intentional managerial interventions, digital technology implementation entails deskilling and/or technological unemployment rather than providing richer dimensions to shopfloor work.
Keywords: 330; e-business; complexity management; work organization; Industry; Hungary; E-Business; Komplexitätsmanagement; Arbeitsorganisation; Industrie; Ungarn